Therapetic experience of hyperbaric oxygenation in ulcerative colğitis refactory to medical treatment (Case report) - Saadettin HÜLAGÜ; Levent DEMİRTÜRK and Melih ÖZEL and Kadir DÜNDAR and Mehmet ALTIN (Turkish Journal of Gastroenterology, 2019)
-